2003
DOI: 10.1081/sim-120024314
|View full text |Cite
|
Sign up to set email alerts
|

Co(II), Ni(II), Cu(II), and Cd(II) Complexes of Some New Arylazopyrazolopyrimidine Derivatives

Abstract: The metal ion complexes [Co(II), Ni(II), Cu(II) and Cd(II)] of some azopyrazolopyrimidine derivatives have been prepared and characterized using elemental analyses, molar conductivity, electronic and IR spectra. The azopyrazolopyrimidines are characterized by a high tendency towards complex formation with the neutral molecules coordinating to the metal ion as bidentate ligands. It is concluded that the ligands are bonded to the metal ion through the a-or b-nitrogen atom of the arylazo group and the carbonyl ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…It was found that they exist in the keto form in solids state while in solution the enol form predominates. 1,14 The visible absorption spectra of 8-[p-substituted phenylazo]-2,4-dimethylpyrazolo[1,5-a]pyrimidine-7(6H)-one derivatives in universal buffer solutions containing different proportions of an organic solvent (methanol, ethanol, acetone, and DMF) show mainly two bands (Figure 1). The shorter wavelength band, appearing at low pH* values (pH* < 6.0), represents absorption by the nonionized species, whereas the longer wavelength band, observed at higher pH* values (pH* > 8.8), is due to the absorption by ionized species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that they exist in the keto form in solids state while in solution the enol form predominates. 1,14 The visible absorption spectra of 8-[p-substituted phenylazo]-2,4-dimethylpyrazolo[1,5-a]pyrimidine-7(6H)-one derivatives in universal buffer solutions containing different proportions of an organic solvent (methanol, ethanol, acetone, and DMF) show mainly two bands (Figure 1). The shorter wavelength band, appearing at low pH* values (pH* < 6.0), represents absorption by the nonionized species, whereas the longer wavelength band, observed at higher pH* values (pH* > 8.8), is due to the absorption by ionized species.…”
Section: Resultsmentioning
confidence: 99%
“…Preparation of Arylazopyrazolopyrimidine Derivatives. 13,14 Each of the resulting azo dyes from the above step was refluxed for 4 h with acetylacetone in the (1:1) molar ratio in 30 mL of acetic acid. The reaction mixture was then cooled to room temperature, whereby a solid compound was precipitated.…”
Section: Methodsmentioning
confidence: 99%
“…In particular p-nitroaniline, m-nitroaniline, p-nitro-N,N-dimethylaniline, and other similar choromophores were found to exhibit rather large NLO properties [10]. Although many Schiff bases derived from aromatic aldehydes and amines and their corresponding metal complexes have been extensively studied, relatively few 2 Journal of Chemistry azo-linked Schiff bases and their metal complexes have been reported [11,12].…”
Section: Introductionmentioning
confidence: 99%